Mapping of Dengue Hemorrhagic Fever Vulnerability Based on Geographic Information Systems in Lubuk linggau City - Sekarrini, Cipta Estri (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The purpose of this paper is to map the level of dengue hemorrhagic fever vulnerability using the Geographic Information System (GIS) in Lubuklinggau. This type of research uses quantitative methods and is carried out in the administrative area of ​​Lubuklinggau City, South Sumatra Province. The type of data used is secondary data obtained from relevant agencies and remote sensing data, there are four input data; the incidence of dengue hemorrhagic fever, temperature, population density, and vegetation density. Data analysis techniques using data analysis using scoring methods with Geographic Information Systems (GIS). The results obtained that the level of DHF vulnerability based on spatial analysis in Lubuklinggau City in 2016 were divided into three classes, namely areas with low vulnerability levels of 5.928,06 ha or 16%, areas with moderate vulnerability levels of 22.903,80 ha or 62%, and areas with a high level of vulnerability are 7.917,97 or 22%. So, the level of vulnerability to dengue disease, the results obtained that the City of Lubuklinggau is at a moderate level of vulnerability.